INTERNALISASI PEMANFAATAN PERMAINAN BALOGO SEBAGAI STIMULASI PEMBELAJARAN AUD DALAM PENGASUHAN KELUARGA BANJAR - Tiara Nur Haliza (STAINU Purworejo, 2022)
The purpose of this study was to determine the internalization of the balogo game as a stimulation of AUD learning in Banjar family care. This research method is using a qualitative approach to the type of qualitative descriptive research. This research was conducted during April 2022. The participants consisted of 6 students, namely 1 boy and 5 girls and one Banjarese family at the PH Clothing Store, Samarinda. The results of the study indicate that it is important to introduce the traditional game of Balogo from Banjar as a learning stimulation for early childhood so that it is not threatened with extinction. This game can train children's cognitive to focus when playing balogo games, train children's fine motor skills when treading balogo sticks, and train children's social-emotional emotions when playing patiently and waiting for their turn.